2021
DOI: 10.3390/vaccines9040406
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Impact of Rotavirus Vaccines in Korea, 2008–2020; Emergence of G8P[8] Strain

Abstract: This study evaluated the long-term impact of rotavirus vaccination on prevalence, seasonality, and genotype distribution in Gwangju, Korea for 13 seasons. Rotavirus was identified using ELISA and then sequenced for G and P genotypes by Reverse Transcription Polymerase Chain Reactions for diarrhoeagenic patient specimens from local hospitals between January 2008 and August2020. Of 26,902 fecal samples, 2919 samples (10.9%) were ELISA positive. The prevalence declined from 16.3% in pre-vaccine era to 5.4% in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…40 The emergence of this unusual G8P [8] in Chiang Rai, Thailand may be a consequence of global vaccine introduction, and this phenomenon has been recently described in multiple reports. 6,7,30,31,35,38 Full genome analysis of four representative G8P [8] strains in the present study exhibited the constellation of genogroup II with the DS-1-like G8-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2, similar with recent RVA investigations from several countries. 7,8,21,30,32,34,35,37,38,[40][41][42] Genetic analysis of the VP7 genes demonstrated that 14 G8P [8] strains in this study and 13 G8P [8] strains previously described in Thailand and China contained two amino acid residues (A125S and N147D) in the neutralizing epitopes different from the prototype G8 strains (Figure 2A).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…40 The emergence of this unusual G8P [8] in Chiang Rai, Thailand may be a consequence of global vaccine introduction, and this phenomenon has been recently described in multiple reports. 6,7,30,31,35,38 Full genome analysis of four representative G8P [8] strains in the present study exhibited the constellation of genogroup II with the DS-1-like G8-P[8]-I2-R2-C2-M2-A2-N2-T2-E2-H2, similar with recent RVA investigations from several countries. 7,8,21,30,32,34,35,37,38,[40][41][42] Genetic analysis of the VP7 genes demonstrated that 14 G8P [8] strains in this study and 13 G8P [8] strains previously described in Thailand and China contained two amino acid residues (A125S and N147D) in the neutralizing epitopes different from the prototype G8 strains (Figure 2A).…”
Section: Discussionsupporting
confidence: 90%
“…Full genome analysis of four representative G8P[8] strains in the present study exhibited the constellation of genogroup II with the DS‐1‐like G8‐P[8]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2, similar with recent RVA investigations from several countries 7,8,21,30,32,34,35,37,38,40–42 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…3,4 Distribution of RVA genotypes in Thailand between 2000 and 2019 showed that G1P [8] was the most prevalent, followed by G9P [8] and G3P [8]. 3,4,[21][22][23][24][32][33][34][35] In Chiang Rai, G9P [8] was predominant in 2015-2016, but the genotype shifted to be the equine-like G3P [8] in the following two seasons during 2016-2018. 3,4 According to previous reports since 2010 in Thailand, G8P [8] strains have been identified with the incidence rates ranging from 3.1 to 22%.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] RVA G8P [8] strains, which are commonly found in cattle, have been frequently detected in humans in the post-vaccination period in many countries, including Argentina, Chile, China, the Czech Republic, Japan, Korea, Singapore, Thailand, and Vietnam. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Surveillance of RVA in Chiang Rai province of Thailand has continuously monitored the diversity and distribution of RVA since 2015 and reported the emergence of G9P [8] in 2015-2016 and the equine-like G3P [8] in 2016-2018. 3,4 The purpose of the present study was to investigate the molecular epidemiology and characterization of RVA strains in children hospitalized with acute gastroenteritis in Chiang Rai, Thailand from 2018 to 2020.…”
Section: Introductionmentioning
confidence: 99%